1999
DOI: 10.1007/bf02287271
|View full text |Cite
|
Sign up to set email alerts
|

The closing of central state hospital: Long-term outcomes for persons with severe mental illness

Abstract: This study examined the clinical/community functioning of long-stay patients following closing of a large state psychiatric hospital. Two overlapping samples were followed: (1) the tracking project collected information on patient location, treatment provision, legal contacts, and level of functioning (LOF) and followed all discharged patients and (2) the research study subsample, drawn from the final group of discharged patients, gathered information on quality of life (QOL), LOF, and general physical and men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 31 publications
0
25
0
Order By: Relevance
“…This finding is in line with a greater risk of suicide among young deinstitutionalized patients served in a community mental health center (Pepper, Kirshner, and Ryglewicz 1981). In contrast, Bachrach (1996) and McGrew et al (1999) reported general improvements in the quality of life and functioning among patients discharged and treated in community settings due to the closure of state psychiatric hospitals.…”
Section: Prior Studies and Limitationsmentioning
confidence: 51%
See 2 more Smart Citations
“…This finding is in line with a greater risk of suicide among young deinstitutionalized patients served in a community mental health center (Pepper, Kirshner, and Ryglewicz 1981). In contrast, Bachrach (1996) and McGrew et al (1999) reported general improvements in the quality of life and functioning among patients discharged and treated in community settings due to the closure of state psychiatric hospitals.…”
Section: Prior Studies and Limitationsmentioning
confidence: 51%
“…The development of psychopharmacology beginning in the 1950s enabled community treatment of severe mental illness and reduced the need for long hospitalization (Morrissey 1989;Mechanic and Rochefort 1990;Grob 2001). With continued advances of psychotropic medications and treatment, community options might achieve similar or improved patient outcomes as suggested by Bachrach (1996) and McGrew et al (1999). In addition to technological innovations, however, strong ideological consensus, regulations of welfare programs such as Medicaid rules, and financial considerations have reportedly served as catalysts for rapid and ongoing public bed reductions (Cameron 1978;Gronfein 1985a;Mechanic and Rochefort 1990;Frank, Goldman, and Hogan 2003;Grob and Goldman 2006).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Although differences in the nature of sexual networks and risk behavior between the two types of settings exist, it is important to remember that it is common for clients with severe and persistent mental illness to move back-and-forth between institutional and community care settings (McGrew et al, 1999;Polgar and Morrissey, 1999). Indeed, the long-term trend towards deinstitutionalization has reduced the typical length of stay in long-term institutions (Dowdall, 1996) and increased the diversity of service settings where consumers receive treatment (Polgar and Morrissey, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…It has been especially driven by humanitarian concerns (Aderibigbe, 1997;Haug and Rossler, 1999;Thornicroft and Bebbington, 1989;Yohanna, 2013) responding to the improper treatment and human rights violations associated with long-term hospitalizations in big psychiatric institutions (Drew et al, 2011). Tens of thousands of long-term patients were discharged from mental hospitals as a consequence of deinstitutionalization (Honkonen et al, 1999;Talbott, 2004;Thornicroft and Bebbington, 1989), including a large number of patients with schizophrenia, some of whom were previously hospitalized for more than 20 years (Andrews et al, 1990;Barr and Parker, 1975;Donnelly et al, 1997;McGrew et al, 1999;Rothbard et al, 1999;Salokangas and Saarinen, 1998).…”
Section: Introductionmentioning
confidence: 99%